Stronger together: perspectives on gratitude social processes in group interventions for adolescents - Wong, Y. Joel; Pandelios, Alexis L.; Carlock, Kane; Thielmeyer, Alexandria M. B. (Frontiers in Psychology, 2024)
Most gratitude interventions for adolescents emphasize private experiences of gratitude (e.g., gratitude journaling), dyadic expressions of gratitude (e.g., writing a gratitude letter to another person), or group-based psychoeducation about gratitude. By contrast, group interventions that emphasize gratitude social processes (GSPs)-interpersonal or group processes that involve or are directly triggered by the disclosure or expression of gratitude to other group members-provide an ideal forum for adolescents to reap the full benefits of gratitude experiences. In this perspective article, we propose a typology of five GSPs-disclosing, expressing, receiving, responding to, and witnessing gratitude in relation to other group members-that operate synergistically to produce positive effects for adolescents. In turn, we theorize that these GSPs likely produce superior outcomes, as compared to other gratitude interventions, through five psychosocial mechanisms of change: observational learning, group cohesion, vicarious gratitude, group-based gratitude, and collective gratitude. Overall, we encourage researchers and practitioners to incorporate GSPs in their gratitude interventions with adolescents.